Concordance Between the Ki-67 Index Cutoff Value of 55% and Differentiation in Neuroendocrine Tumor and Neuroendocrine Carcinoma in Grade 3 Pancreatic Neuroendocrine Neoplasms. Issue 10 (November 2020) - Shi, Huiying; Chen, Luohai; Zhang, Qin; Lin, Yuan; Jiang, Chen; Yao, Hailing; Hou, Xiaohua; Chen, Minhu; Lin, Rong; Chen, Jie
Abstract : Objective: In 2017 and 2019, the World Health Organization defined grade 3 neuroendocrine tumors (G3 NETs) and neuroendocrine carcinoma (G3 NEC) in the pancreas. The validity of this classification remains to be verified. Methods: Clinical data were collected and analyzed for 39 G3 pancreatic neuroendocrine neoplasms (PanNENs) patients between 2009 and 2018. Results: The tumor-node-metastasis stage ( P = 0.0260), differentiation ( P = 0.0115), and Ki-67 index ( P = 0.0371) are prognostic factors for G3 PanNENs by Kaplan-Meier survival analysis. Among 39 patients, 18 had a Ki-67 index of less than 55% and well-differentiated morphology (G3 NET) and 16 had a Ki-67 index of 55% or greater and poorly differentiated morphology (G3 NEC). Grade 3 neuroendocrine tumor had a significant better prognosis than G3 NEC (median overall survival time, 25 months [95% confidence interval, 10.854–39.146 months] vs 12 months [95% confidence interval, 6.316–17.684 months], P = 0.0164). Based on Cox regression analyses, tumor-node-metastasis stage ( P = 0.016) was identified as the independent prognostic factor for G3 PanNENs. Conclusions: The upper Ki-67 index cutoff of 55% might be the best cutoff value to define G3 NETs and G3 NECs for G3 PanNENs. The World Health Organization 2017 and 2019 classification system for G3 PanNENs can identify high-risk patients with G3 PanNENs. Abstract : Supplemental digital content is available in the text.